Two Facets of ‘Southern Opening’: Bilateral Relations Between Angola and Hungary in the 70s-80s and Post 2015 - Hegedus, Eva (Journal of Central and Eastern European African Studies, 2024)
The new strategy of ‘Southern Opening’, announced in 2015, has put Africa again in the focus of Hungary’s foreign policy, with Angola being among the priority countries. The reopening of the embassy in Luanda in 2017 and the Hungarian Foreign Minister’s visit in 2018 were further symbolic steps in recognizing Angola’s importance as a potential regional power and a strategic partner in the sub-Saharan region. Bilateral cooperation dates back to much earlier, the late 60s, however, spanning through nearly two decades during the socialist era of both countries’ history. Hungary has provided sizable military aid (to the MPLA), actively ‘exported’ goods, technology, and knowledge through sending experts and offering scholarships, and received wounded soldiers for treatment and rehabilitation. After the mid-90s, bilateral relations have stagnated up until the new turn to the South from 2015. Building on national archive documents and personal accounts of experts and diplomats, this paper presents the heyday of bilateral cooperation in the 70s and 80s. It also gives an overview of the revitalising relations; and analyses how those may fit in the new foreign policy agenda and promotion of Hungarian economic interests in Angola.. The People’s Republic of Hungary was also involved in the ʻsocialist scramble for Africa’. Angola seemed to be the targeted country in the region mentioned above, but in the 1960s another opportunity emerged, namely Namibia. This large, sparsely inhabited country was under South African rule, although the Ovambo, a majoritarian ethnic group, was fighting for independence. Their organisation was known as the SWAPO. This study aims to describe how the Hungarian socialist leadership and the leaders of SWAPO found a way to cooperate with each other. The original documents quoted in this study are from the Hungarian National Archives and the daily newspapers between the 1960s and 1980s, and they have been cited to assist the readers in following the development of the relations.